1985
DOI: 10.1002/crat.2170200614
|View full text |Cite
|
Sign up to set email alerts
|

L‐alanine distribution in the growth pyramids of TGS crystals and its influence on the growth, switching and domain structure

Abstract: l'lic full-faccd crystals of triglycinc sulphate (TGS) and deuterated hornologs substituted by I4-a1aniiio (LATGS arid LADTGS, resp.) wcrc grown from growth solutions with various concentratloris of the sribstituerit. The distribution of L, alanirie (L,al) in various growth pyramids of crystals was measured by the electrical switching method. Tho stability of domain structure of doped crystals was studied by the liquid crystal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 13 publications
3
21
1
Order By: Relevance
“…The sample surfaces perpendicular to their ferroelectric axis were covered by evaporated silver (849) electrodes. LTTGS crystals grow along the "b" axis asymmetrically with respect to the nucleus, similarly as it has been observed for LATGS [3,4], DATGS [5], LSTGS [6] and DSTGS [7] crystals.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…The sample surfaces perpendicular to their ferroelectric axis were covered by evaporated silver (849) electrodes. LTTGS crystals grow along the "b" axis asymmetrically with respect to the nucleus, similarly as it has been observed for LATGS [3,4], DATGS [5], LSTGS [6] and DSTGS [7] crystals.…”
Section: Methodssupporting
confidence: 71%
“…Owing to this phenomenon dielectric parameters of the admixtured crystals undergo only slight changes in the process of spontaneous ageing, which is of particular importance in the application of TGS crystals. So far the influence of such admixtures as L-and D-alanine [1][2][3][4][5], L-, D-, DL-serine [6][7][8], L-valine [12], phosphaglycine [9] and haloacetamide [10] on physical properties of TGS crystals has been studied. This paper presents results of investigation of L-threonine admixture on dielectric properties of TGS crystals (LTTGS).…”
Section: Introductionmentioning
confidence: 99%
“…TGS crystals with D-serine admixture grow asymmetrically with respect to the seed along "b" axis similarly as it was observed for L-serine TGS crystal, though the asymmetry was now found to develop in the opposite direction. Asymmetry of the same kind was also observed for TGS crystals admixtured with L-α-alanine [4,6,10,11] as well as D-α-alanine [11].…”
Section: Introductionsupporting
confidence: 49%
“…Nakatani [5,6] has studied the distribution of the bias field in the TGS crystals admixtured with L-α-alanine and DL-α-alanine and has reported that Eb is not homogeneous within a growth pyramid and its values are higher on the -b side than on the +b side in accordance with Refs. [10,12]. The changes in the Eb values correspond to the changes in the alanine admixture concentration in the crystal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation